2006
DOI: 10.1021/pr050435r
|View full text |Cite
|
Sign up to set email alerts
|

2-D DIGE Analysis of Butyrate-Treated HCT-116 Cells after Enrichment with Heparin Affinity Chromatography

Abstract: Butyrate, a 4-carbon short chain fatty acid, is responsible for the protective effects of fiber in colorectal cancer prevention. To better understand the 'blueprint' of butyrate's chemopreventive role in this disease, we performed 2-dimensional difference gel electrophoresis (2-D DIGE) of butyrate-treated HCT-116 colorectal cancer cells after pre-fractionation using heparin affinity chromatography. A combination of this enrichment step with overlapping narrow range IPGs (pH 4-7 and pH 6-11) in 2-D DIGE resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…Interestingly a subset of proteins found in this study had also been identified in our previous work using 2-D DIGE (17), and they showed regulation in a similar manner by butyrate treatment. Such proteins include cytoskeletal 8, ornithine aminotransferase, cytochrome c oxidase polypeptide VIb, and Tu elongation factor.…”
Section: Protein Identification From Itraq-and Icat-labeled Peptidessupporting
confidence: 84%
See 3 more Smart Citations
“…Interestingly a subset of proteins found in this study had also been identified in our previous work using 2-D DIGE (17), and they showed regulation in a similar manner by butyrate treatment. Such proteins include cytoskeletal 8, ornithine aminotransferase, cytochrome c oxidase polypeptide VIb, and Tu elongation factor.…”
Section: Protein Identification From Itraq-and Icat-labeled Peptidessupporting
confidence: 84%
“…Cell Culture-HCT-116 colorectal cancer cells were cultured and treated with 5 mM sodium butyrate as reported previously except that three treatment time points (24,36, and 48 h) were used (17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subcellular localization of hnRNP A1 is dictated by the phosphorylation status of its C terminus, which affects the Trn1-dependent nuclear import of hnRNP A1. 20 The phosphorylation of hnRNP A1 occurs under conditions of diverse stresses such as osmotic shock, 19 UV irradiation, 19 heat shock, 35 or treatment of cells with sodium butyrate 36 and arsenite. 35 Cytoplasmic hnRNP A1 accumulates in stress granules, the sites of mRNA triage from which target mRNAs are exported to processing bodies for degradation.…”
Section: Discussionmentioning
confidence: 99%